Ferritin Protein Regulates the Degradation of Iron Oxide Nanoparticles. Issue 2 (7th November 2016) - Volatron, Jeanne; Carn, Florent; Kolosnjaj‐Tabi, Jelena; Javed, Yasir; Vuong, Quoc Lam; Gossuin, Yves; Ménager, Christine; Luciani, Nathalie; Charron, Gaëlle; Hémadi, Miryana; Alloyeau, Damien; Gazeau, Florence
Abstract : Proteins implicated in iron homeostasis are assumed to be also involved in the cellular processing of iron oxide nanoparticles. In this work, the role of an endogenous iron storage protein—namely the ferritin—is examined in the remediation and biodegradation of magnetic iron oxide nanoparticles. Previous in vivo studies suggest the intracellular transfer of the iron ions released during the degradation of nanoparticles to endogenous protein cages within lysosomal compartments. Here, the capacity of ferritin cages to accommodate and store the degradation products of nanoparticles is investigated in vitro in the physiological acidic environment of the lysosomes. Moreover, it is questioned whether ferritin proteins can play an active role in the degradation of the nanoparticles. The magnetic, colloidal, and structural follow‐up of iron oxide nanoparticles and proteins in lysosome‐like medium confirms the efficient remediation of potentially harmful iron ions generated by nanoparticles within ferritins. The presence of ferritins, however, delays the degradation of particles due to a complex colloidal behavior of the mixture in acidic medium. This study exemplifies the important implications of intracellular proteins in processes of degradation and metabolization of iron oxide nanoparticles. Abstract : Proteins implicated in iron homeostasis might be involved in the cellular processing of iron oxide nanoparticles . The capacity of ferritin cages to accommodate and store the degradation products of nanoparticles is investigated in vitro in the physiological acidic environment of the lysosomes. Ferritin is shown to play a regulatory role into the degradation of iron oxide nanoparticles and to serve as recycling cages for iron ions released by nanoparticles.